Pengaruh Metode Demonstrasi Pada Meteri Gambar Dekoratif Terhadap Hasil Belajar Peserta Didik Kelas III SD Negeri Garot Aceh Besar - Putri Nur Yasmin; Aida Fitri; Mislinawati Mislinawati (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study was conducted to determine the effect of the demonstration method on decorative picture material on the learning outcomes of third graders at SD Negeri Garot Aceh Besar. This type of research uses a quasi-experimental design (pre-experimental) with one group pre-and post-testing. The data collection approach uses tests (pretest and posttest). The population in this study were third-grade students at SD Negeri Garot Aceh Besar and the sampling strategy was purposive sampling. The sample of this study consisted of 30 students in class III-a. The threshold of significance = 0.05 and dk = N-1 = 29. From the data analysis, the t-count and t-table become 28.86 and 1.70. Therefore, H0 is rejected while H1 is approved. This study concludes that the application of the demonstration learning method has an effect on the learning outcomes of class IIIa students at SD Negeri Garot Aceh Besar on the decorative picture material